INFORMATIONAL ENSURING OF PRODUCTION EXPENSES AUDIT - Ніконович, М. О. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The main sections of the accounting of the production expenses, which can be used as the informational basis for the audit evidences and the procedure of their obtaining, are determined in the article. The recommendations regarding the receipt and assessment of evidences for the effectiveness of internal system of production expenses control are given.